Assessing the impact of short-term Lugol’s solution on toxic nodular thyroid disease: a pre-post-intervention study - Hedberg, Fredric; Cramon, Per Karkov; Bränström, Robert; Falhammar, Henrik; Calissendorff, Jan (Frontiers in Endocrinology, 2024)
Preoperative iodine therapy in toxic nodular goiter (TNG) is discouraged as iodine may cause aggravation of hyperthyroidism. We aimed to examine if a short course of iodine treatment is safe to administer in TNG.Patients with TNG (n=20) and subclinical to mild hyperthyroidism (free (f)T4 <30 pmol/L) without complicating illnesses were included in this pre-post-intervention study at Karolinska University Hospital. All participants received Lugol's solution 5%, three oral drops thrice daily for 10 days. Heart rate, TSH, fT4, fT3 concentrations were collected before (day 0) and after treatment (day 10). Thyroid hormone concentrations were also measured at two time points during treatment to discover aggravations of hyperthyroidism. ThyPRO39se, a qualityof-life questionnaire, was filled out day 0 and day 10. Differences in heart rate, thyroid hormone concentrations, and quality-of-life before and after treatment were compared. Adverse reactions were reported.The median age was 63.5 years. Female to male ratio 19:1. FT4 and fT3 concentrations decreased (both p<0.001), and TSH concentration increased (p<0.001) after 10 days of treatment. There was no difference in heart rate. No aggravations of thyrotoxicosis were noticed in any of the participants. ThyPRO39se scores improved on three scales, including hyperthyroid symptoms, while the remaining scale scores were unchanged. Mild and transient symptoms related to or possibly related to treatment were observed in six participants.A short course of Lugol's solution improved thyroid hormone concentrations, reduced patient-reported hyperthyroid symptoms and was safe in TNG. Lugol's solution might be an option for preoperative treatment in TNG. Clinical trial registration https://www.clinicaltrials.gov, identifier NCT04856488.